Televisão interativa: inclusão e alternativas na digitalização - Rosa, Ana Maria Oliveira (Universidade do Vale do Rio dos Sinos, 2010)
This thesis is inserted in the ambit of Political Economy of Communication, pursuing, through the correlation between theoretical discussions and empirical data, to understand the process of development of the interactivity on Brazilian television. The research focus involves the conceptualization of interactivity itself, related to digital TV, an investigation of the key elements to create an interactive program aiming social and digital inclusion and the issue of the relation between changes in the audiovisual product caused by the interactivity and changes in the current TV market. The study was performed to present a broad understanding of interactivity, including its use in other areas of communication, as well as revisiting experiences from analog television. There are also observations about the processes of implementation of the Japanese-Brazilian digital television standard, as well as the middleware Ginga, pointing links among this processes, political decisions and economic forces. The characterization of the television oligopoly is presented at various points of the thesis, including the consideration of interactivity projects offered by the broadcasters, designed to maintain their own techno-esthetic standard. As result of the considerations, it was created a prototype of an interactive television program, Comunidade Ativa, in order to be collaborative. Concluding, it is argued that technology is only part of the suggested changes, importing more than that matters related to economics and politics of the country, such as the partnership between companies, that exploit the television, and the governments, on the basis of power strategies; and related to the strengthening of civil society, one way to combat the recurring impasses in democratizing communication.
Keywords: Televisão digital; Interatividade; Inclusão sócio-digital; Colaboração; Economia Política da Comunicação; Digital television; Interactivity; Social and digital inclusion; Collaboration; Political Economy of Communication; ACCNPQ::Ciências Sociais Aplicadas::Comunicação